Development of the novel ACLY inhibitor 326E as a promising treatment for hypercholesterolemia - Zhifu Xie; Mei Zhang; Qian Song; Long Cheng; Xinwen Zhang; Gaolei Song; Xinyu Sun; Min Gu; Chendong Zhou; Yangming Zhang; Kexin Zhu; Jianpeng Yin; et al. (Elsevier, 2023)
Hepatic cholesterol accumulation is an important contributor to hypercholesterolemia, which results in atherosclerosis and cardiovascular disease (CVD). ATP-citrate lyase (ACLY) is a key lipogenic enzyme that converts cytosolic citrate derived from tricarboxylic acid cycle (TCA cycle) to acetyl-CoA in the cytoplasm. Therefore, ACLY represents a link between mitochondria oxidative phosphorylation and cytosolic de novo lipogenesis. In this study, we developed the small molecule 326E with an enedioic acid structural moiety as a novel ACLY inhibitor, and its CoA-conjugated form 326E-CoA inhibited ACLY activity with an IC50 = 5.31 ± 1.2 μmol/L in vitro. 326E treatment reduced de novo lipogenesis, and increased cholesterol efflux in vitro and in vivo. 326E was rapidly absorbed after oral administration, exhibited a higher blood exposure than that of the approved ACLY inhibitor bempedoic acid (BA) used for hypercholesterolemia. Chronic 326E treatment in hamsters and rhesus monkeys resulted in remarkable improvement of hyperlipidemia. Once daily oral administration of 326E for 24 weeks prevented the occurrence of atherosclerosis in ApoE−/− mice to a greater extent than that of BA treatment. Taken together, our data suggest that inhibition of ACLY by 326E represents a promising strategy for the treatment of hypercholesterolemia.